Stakeholders' perceptions on sustainability transition pathways of the cocoa value chain towards improved livelihood of small-scale farming households in Cameroon - Vogel, C.; Mathé, S.; Geitzenauer, M.; Ndah, H.T.; Sieber, S.; Bonatti, M.; Lana, M. (Informa UK Limited, 2020)
Given the persistent poor livelihood of cocoa-farming households, future climate predictions and the worldwide demand pressure for higher cocoa quality and productivity, there is still a strong need to find new approaches that guarantee a sustainable cocoa future in cocoa-producing countries amongst which Cameroon is one of them. This exploratory research investigates potential future pathways for the cocoa sector in Cameroon by mapping the perceptions of actors involved in the socio-technical regime. Qualitative expert interviews, structured questionnaires and field observation, as well as a focus group discussion have been applied to understand how a sustainability transition can be triggered. The study shows that actors envisage a sustainability change which determines their actions; however, their perceptions towards future transitions are not actively coordinated. Actors are not finding a way of adopting new organizational structures and letting a transition occur effectively, like in the case of certification standards. An alignment of perceptions and activities, and a stronger cooperation between the private and public are strongly recommended. The study encourages to consider a coordination of actors’ perceptions towards future scenarios as a starting point to study sustainability transitions.